Portrait of Max Ernst - Carrington, Leonora, b 1917 (Slide Library, Department of Visual Arts, Brigham Young University, 1939)
Surrealist portrait of the artist Ernst , with whom Carrington had a relationship, he is standing ins a fluffy feathered robe in arctic landscape with a frozen white horse on the left. British; Electronic Reproduction; 50 x 27 cm